2022
DOI: 10.1108/mf-12-2021-0602
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic factors, R&D expenditure and research productivity in economics and finance

Abstract: PurposeDrawing on institutional theory and knowledge spillover, the study aims to examine whether there is a causality relationship between macroeconomic factors and research productivity.Design/methodology/approachThe study uses fixed-effects (FE) panel regression analysis, utilizing 1,614 country–year observations and 541,732 citable publications between 1996 and 2017, to explore the relationship between macroeconomic factors, research and development (R&D) expenditure and research productivity in econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…The second important result is that as R&D expenditures increase, the performance of countries also increases. This result supports the research of Gulbrandsen and Smeby (2005), Solarin and Yen (2016), Lee (2021), Teitel (1994), Meo et al (2013), and Uyar et al (2022). Another important result obtained from the correlation analysis is that research performance increases with the increase in the level of development of countries.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The second important result is that as R&D expenditures increase, the performance of countries also increases. This result supports the research of Gulbrandsen and Smeby (2005), Solarin and Yen (2016), Lee (2021), Teitel (1994), Meo et al (2013), and Uyar et al (2022). Another important result obtained from the correlation analysis is that research performance increases with the increase in the level of development of countries.…”
Section: Discussionsupporting
confidence: 83%
“…This study analyses the research performance of OECD countries and also examines the relationship between research performance and certain variables. Previous studies have shown that research performance increases with an increase in R&D expenditures (Gulbrandsen & Smeby, 2005; Lee, 2021; Meo et al, 2013; Solarin & Yen, 2016; Teitel, 1994; Uyar et al, 2022). Another variable related to research performance is the level of development of countries.…”
Section: Introductionmentioning
confidence: 99%